Distribution, Coexistence, and Decline of Moroccan Large Branchiopods. Issue 3 (1st May 2015) - van den Broeck, Maarten; Waterkeyn, Aline; Rhazi, Laila; Brendonck, Luc
Abstract: An extensive field survey was conducted between 2012 and 2014 to update the knowledge on the diversity and distribution of large branchiopods in northwestern Morocco. Historical data were available from the 1980s to allow comparison with our current survey, but most exact locations of previously sampled large branchiopod populations were unknown. Fifteen (of the known 17) Moroccan large branchiopod species (9 Anostraca, 3 Notostraca, and 3 Spinicaudata) were recovered during our survey, including two endemic species for Morocco ( Linderiella africana and Tanymastigites brteki ). When comparing our results with historical data, a general decline in habitat numbers and species richness per habitat over the last 30 years becomes apparent. Although northwestern Morocco can still be considered a hotspot for large branchiopods, conservation measures should be taken to prevent further loss of biodiversity.